Introduction Pages - Radu E. SESTRAS (Notulae Scientia Biologicae, 2018)
Notulae Scientia Biologicae (http://www.notulaebiologicae.ro), Issue 1, Volume 10, 2018: The papers published in this issue (http://www.notulaebiologicae.ro/index.php/nsb/issue/current) represent interesting novelties in different topics of life science. Among the exciting researches, we invite you to find news about enhancing the resistance of watermelon; biodiversity within Mt. Hamiguitan Range Wildlife Sanctuary; bioactive compounds investigated in several species (Litsea glutinosa, Senna alata, etc.); new approaches for technical aspects for improving crops of interest (mass production of Spirulina, gamma radiation treatments on potato and sesame, testing banana peel as substrate); cytogenetic, forestry and carbon sequestration; reproductive behavior with significant embryological data. Notulae Scientia Biologicae journal has moved to online-only publication at the start of 2017. At the same time, we maintain our standard publication, as printed form, with 'classic' style - volume, issue, pagination.